Regulation of bone health through physical exercise: Mechanisms and types - Chang, Xinyu; Xu, Sheng; Zhang, Hao (Frontiers in Endocrinology, 2022)
Osteoporosis, characterized by bone mineral density reduction, bone mass loss, increased bone fragility, and propensity to fractures, is a common disease in older individuals and one of the most serious health problems worldwide. The imbalance between osteoblasts and osteoclasts results in the predominance of bone resorption and decreased bone formation. In recent years, it has been found that regular and proper exercise not only helps prevent the occurrence of osteoporosis but also adds benefits to osteoporosis therapy; accordingly, bone homeostasis is closely associated with mechanical stress and the intricate crosstalk between osteoblasts and osteoclasts. In this review, we summarize the mechanisms of exercise on osteoporosis and provide new proposals for the prevention and treatment of osteoporosis.